Aplikasi Pendaftaran Siswa pada Bimbel Berbasis Web: Studi Kasus pada Bimbel SEC - Muhammad Razka Saputra; Mamok Andri Senubekti; Novita Anggraini (Melati Institute, 2023)
Human tutoring is widely believed to be the most effective form of teaching in the world, and experimental work confirms that expert tutors can produce huge learning gains. Bimbel Succes Education Club is a tutoring place and also accepts private tutoring to participants' homes, this tutoring course is also for all levels of general education, such as calistung, elementary and high school. The registration and payment process is still relatively manual. With this problem the owner, took the initiative to carry out technology-based development with this the author provides a solution to build a website-based application as a registration medium and allows it to reach as many potential registrants as possible. With this website-based registration application with the bootstrap framework, the author hopes that this application can be a solution to the owner's problem. To support this research, data collection methods are carried out by observation, interviews, and literature studies that interact with the owner at the same time.